2014
DOI: 10.1039/c3cp55255a
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the Fischer–Tropsch process using zeolites for tail gas separation

Abstract: This work is aimed at optimizing a Fischer-Tropsch Gas To Liquid (GTL) process by recycling compounds of the expelled gas mixture using zeolites for the separation. To that end, we have performed a computational study on four structures widely used in industry. A range of Si/Al ratios have been explored and the effects of their distribution assessed. The ability of the considered force fields and molecular models to reproduce experimental results has been widely proved in previously reported studies. Since thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The adsorption capacity of MFI-type zeolites is known to be cation-dependent in aluminum-containing frameworks. In a previous study, we have shown for some T-sites that this dependence lies not in the sodium cation distribution but in their number . In this study, we have expanded the scope to all T-sites.…”
Section: Mfi-type Structures With Sodium Cationsmentioning
confidence: 94%
“…The adsorption capacity of MFI-type zeolites is known to be cation-dependent in aluminum-containing frameworks. In a previous study, we have shown for some T-sites that this dependence lies not in the sodium cation distribution but in their number . In this study, we have expanded the scope to all T-sites.…”
Section: Mfi-type Structures With Sodium Cationsmentioning
confidence: 94%
“…The dual- adsorption ratios, or the stoichiometric adsorption properties of the material, play a critical role in the conversion efficiency. 42,43 Perez-Carbajo et al 44 recently demonstrated that IAST could reasonably describe the mixed adsorption of a ve-component mixture (CO 2 , CH 4 , CO, N 2 and H 2 ) within a range of zeolites (FAU, MFI, MOR and DDR) up to 100 bar. A large change in entropy and enthalpy upon adsorption will cause the reactants to bind into position and their internal bonds to become strained in preparation for reaction.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…By considering solution thermodynamics the Ideal Adsorbed Solution Theory (IAST) was developed by Myers and Prausnitz to predict the adsorption equilibria of binary mixtures. 42,43 Perez-Carbajo et al 44 recently demonstrated that IAST could reasonably describe the mixed adsorption of a ve-component mixture (CO 2 , CH 4 , CO, N 2 and H 2 ) within a range of zeolites (FAU, MFI, MOR and DDR) up to 100 bar. In this study we also consider light gas adsorption within zeolites with minimal surface heterogeneity where IAST is applicable.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Molecular simulations are an extensively used tool to predict the thermodynamic properties of a wide diversity of systems . Molecular simulations have been extensively used to predict the adsorption properties of hydrocarbons in zeolites and other nanoporous materials. Commonly, Monte Carlo simulations (MCs) in the grand-canonical ensemble (GCMC) can be used to compute sorbate loadings in a zeolite for different temperatures and pressures. Several studies where MCs are used to study adsorption of aromatics in zeolites can be found in the literature. , Most molecular simulation studies of adsorption of hydrocarbons in zeolites have focused on adsorption from a vapor phase . This is due to the difficult insertion and deletion of molecules at conditions close to saturation, leading to inefficient simulations .…”
Section: Introductionmentioning
confidence: 99%